The enhancement of epoxidized natural rubber /ethylene vinyl acetate /carbon nanotubes nanocomposites by irradiation - Norazlina binti Mohamad Yatim (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The effect of CNTs as nanofiller in Epoxidized Natural Rubber/Ethylene Vinyl Acetate (ENR/EVA) blend and the effect of irradiation on the newly developed nanocomposites were investigated. CNTs were used as nanofiller in order to replace carbon black where the later's usage have several disadvantages including its pollutive prone production. Besides, carbon black have to be used in high amount and often looked upon as quality enhancing material, but not as cost cutting ones. In this research, CNTs were added to ENR50 followed by the addition of EVA to produce ENR/EVA/CNTs nanocomposites. CNTs at various amount (2, 3, 4 and 6 wt%) were incorporated into ENR50 by solvent casting method. The ENR/CNTs were blended with EVA by mixing in a Brabender Plasticoder at 120°C. The samples were finally irradiated by using electron beam at 3 MeV in a dose range of 50 to 200 kGy. Radiation vulcanization was selected because it is a non radioactive method and safe to handle compared to the conventional method of sulphur vulcanization which suffers from several disadvantages such as the presence of nitrosoamine compounds and high cytotoxicity. Results showed that the mechanical properties and the thermal stability of the nanocomposites increased with the increase in CNTs. This was attributed to the well-dispersed CNTs nanofillers in the rubber particles. The analyses using SEM, TEM, FTIR and XRD had confirmed the highly homogeneous of CNTs nanofillers in ENR/EVA matrix. Result on dynamic mechanical analysis revealed that the nanocomposites were compatible at all wt% of CNTs. Meanwhile, the introduction of electron beam irradiation on ENR/EVA/CNTs nanocomposites has resulted in the irradiation-induced crosslinking and this lead to further improvement in the mechanical properties and the compatibility. With regard to mechanical testing, the irradiation modification of ENR/EVA/CNTs nanocomposites has increased the tensile strength (Ts) and modulus at 100% elongation (M100) almost 2 times up to 150 kGy dose of radiation, and a downward trend thereafter. Results on gel fraction analysis further confirmed the occurance of crosslinking in the samples. In addition, the structure and morphology of reinforced ENR/EVA/CNTs nanocomposites was investigated by SEM, TEM, FTIR and XRD in order to gain further evidence on the radiation-induced crosslinking. It can be concluded that CNTs nanofillers acted as the reinforcement agent in ENR/EVA blends which reflected in better mechanical and thermal properties. Besides, the powerful energy of electron beam radiation result in irradiation-induced crosslinking and deformation of ENR50 by shear cutting them in EVA matrix. Formation of finer vulcanized rubber particles and restriction of mobility due to the presence of crosslinks has improved the stability and subsequently lead to a further enhancement in the mechanical properties and compatibility of the nanocomposites.